(untitled) (Heritage, 2023)
The subject of analysis of this paper is the phenomenon of “Albanianism”, which has, in recent centuries, manifested itself in numerous forms, but also crystallized itself as one of the most enduring cohesive factors in constituting Albanian national unity and Albanian irredentist policy. The paper analyzes the influences on the Albanian national consciousness left by the memorialization of the Albanian medieval great Skenderbeg, and the legacy of the “League of Prizren”, which is a symbol of the first concrete Albanian political strategy with expansionist potential. The emphasis is on the analysis of the concept of “Albanianism”, which entered the political life of Albania in the early phase of the so-called “Albanian national awakening” (Rilindja Kombëtare) and which has remained an indispensable element in the political agenda not only of the host state, but also in the nationalist-oriented Albanian diaspora. The aim of this research is to point out the fact that throughout the history of the Albanian state “Albanianism” has been a resistant constantthat successfully served to put aside numerous Albanian antagonisms, be they tribal, confessional or cultural.